CALL #FROG2023: "Money & Games" vom 13. bis 15. Oktober 2023, im Wiener Rathaus - Katharina Kaiser-Müller (Medienimpulse, 2023)
While thousands of enthusiastic players are gathering annually at the Game City in the Vienna City Hall, the FROG invites to an academic discourse on the subject of games and play. This year the conference addresses issues of “Money & Games” in the field of play & games and invites game scholars, creators, youth workers, activists and enthusiasts from around the globe to come together and “follow the money” by discussing the traces it leaves on the field of games & play. Contributions can be submitted until September 1st 2023.